2012
DOI: 10.1363/3813312
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Expanding the Medication Abortion Provider Base in India to Include Ayurvedic Physicians and Nurses

Abstract: Findings support amending existing laws to improve women's access to medication abortion by expanding the provider base to include ayurvedic physicians and nurses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 11 publications
0
40
0
Order By: Relevance
“…One RCT included ANMs and nurses, one RCT included nurse‐midwives (NMWs), and a third RCT included nurses, all compared with doctors. The prospective cohort study from India reported on the provision of medical abortion by Ayurvedic doctors (non‐conventional therapies doctors in the Indian system of medicine) or nurses, compared with doctors . The results from one RCT comparing midwife treatment of incomplete miscarriage with treatment by doctors were reported in two publications, covering effectiveness and safety, and satisfaction and acceptability outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One RCT included ANMs and nurses, one RCT included nurse‐midwives (NMWs), and a third RCT included nurses, all compared with doctors. The prospective cohort study from India reported on the provision of medical abortion by Ayurvedic doctors (non‐conventional therapies doctors in the Indian system of medicine) or nurses, compared with doctors . The results from one RCT comparing midwife treatment of incomplete miscarriage with treatment by doctors were reported in two publications, covering effectiveness and safety, and satisfaction and acceptability outcomes, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The specific medical TOP or medical treatment of incomplete miscarriage regimens used differed across studies, but within each study all providers offered the same treatment regimens. Three RCTs, and one prospective cohort study, reported on treatment with combined mifepristone and misoprostol regimens for induced TOP with maximum gestational age of 63–70 days (mean 6.4–7.6 weeks of gestation). One RCT used 600 micrograms of oral misoprostol to treat incomplete miscarriage when uterine size was assessed to be below 12 weeks of gestation (mean 8.8 weeks of gestation) (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…Several studies conclude that even though abortion providers discuss contraception with their patients, it is common for patients to refuse any form of contraception following an abortion 25 26. The quality of provider counselling and patient education is important for the successful integration of new hormonal methods of contraception into clinical practice 27.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in India have shown that provision of medical abortion services by nurses and Ayurved physicians is equally safe, effective and acceptable to women as provided by certified MBBS physicians, 9 but there is little evidence about whether such provision is acceptable to a range of providers, from trained physicians to nurses and AYUSH physicians themselves. This paper contributes to this unexplored dimension.…”
Section: Discussionmentioning
confidence: 99%